Studies on terrein as a new class of proteasome inhibitors - Demasi,M. (2010)
The proteasome is an intracellular multicatalytic protease involved in the cell cycle regulation, signaling response, antigen presentation and apoptosis. Since proteasome inhibitors promote cell death by apoptosis, they have been proposed as new anti-tumoral drugs. Terrein, a secondary metabolite secreted by the fungus Aspergillus terreus, was firstly described in 1935. In the present work we report that terrein isolated through the screening for inhibitors of the 20S proteasome showed inhibitory effect upon both chymotrypsin- and trypsin-like activities of the multicatalytic core particle, the 20S proteasome. Despite of the high inhibitory concentration determined in vitro, that verified by incubating cells (fibroblasts and a pulmonary tumor cell line) in the presence of terrein was 4-fold lower indicating the proteasome as a selective intracellular target. Moreover, terrein promoted apoptotic cell death on both fibroblasts and pulmonary tumor cell line tested. Although terrein concentrations (mM range) necessary to elicit apoptosis in the cellular models herein tried were high when compared to those (μM and nM range) of other inhibitors recently described, its chemical structure is not correlated to any other inhibitor reported thus far. Therefore, the present results point out for the possibility of exploring terrein as a new molecular fragment for the development of synthetic proteasome inhibitors.